High literacy level, very low reading culture: an examination of the underlying causes of the Zimbabwean paradox - Makaudze, Godwin; Kangira, Jairos (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
Zimbabwe currently boasts of one of the highest literacy levels in Africa. Paradoxically, such an encouraging state of affairs is not paralleled with a high reading culture. Instead, the high levels of literacy are undone by a very low reading culture. This paper is an exploration of the possible underlying causes of such a state of affairs as well as the possible intervention strategies. It used the qualitative paradigm, with interviews and semistructured questionnaires being employed to extract information from selected teachers, learners, parents, readers, publishers and bookshop managers. For teachers, learners, readers and parents, random sampling was used whilst purposive sampling was used for publishers and bookshop managers. Data was discussed in accordance with the themes that emerged. The paper observed that the reasons of the paradox included: emphasis on passing the examination, high costs of living and of producing and accessing reading literature, paucity of serious works of art that illuminate life. Possible intervention strategies included: re-orienting the education system, partnerships meant to avail and subsidise accessibility of literature, re-orienting the Zimbabwean language policy and improving marketing strategies for literature.